GRICEAN MAXIMS AS AN ANALYTICAL TOOL IN TRANSLATION STUDIES: QUESTIONS OF ADEQUACY - Rochayah Machali (TEFLIN, 2012)
One of the many interests in translation studies is to study how meaning is rendered in the target language text (TLT). This is often observed in terms of âequivalence of meaningâ as it is meaning that is being transferred. Equivalence can occur at any level: word, group, sentence, text, and even pragmatic level. On working at the pragmatic level a translator often has to refer to the (immediate) context in order that his/her translation can be understood by the TL readers. When the resulted translation is then analysed in terms of how the âpragmatic meaningâ has been rendered in the TLT, one of the analytical tools that can be used is the Gricean Maxims. In recent years, there have been renewed interests in the studies and researches related to the Gricean maxims. However, none has been concerned with Indonesian context. This article is, therefore, a preliminary inquiry into this area, particularly to see how the maxims can be problematic when we are faced with concepts of politeness.